Investigation of Stress Intensity Factor for Corrugated Plates with Different Profiles Using Extended Finite Element (XFEM) - Nama, Sabreen Saad; Laftah, Rafil Mahmood (Basrah Journal for Engineering Sciences, 2018)
Corrugated plates play very important role in various engineering applications. The occurrence of crack in the body of corrugated plate might results in catastrophic failure. In the present paper there are different profiles of corrugated plates (trapezoidal, sinusoidal and triangle) that are studied. In each profile the stress intensity factor and shape factor were calculated for various crack orientations, various corrugation angles and different curvature radius for the same profile. They are all subjected to different loading conditions using Extended Finite Element Method (XFEM). It is found the stress intensity factor when load applied parallel to corrugation direction is higher when load applied perpendicular to corrugation direction. Also found that the stress intensity factor increase by 115% when curvature radius increases with the load applied perpendicular to corrugation. This study also found and explained that the stress intensity factor increases slightly when the corrugation angle of triangle corrugated plate increases. In all cases studied, the trapezoidal corrugated plate shows the lower values of stress intensity factor compared to the sinusoidal and triangle corrugated plates.